Universal procedures for spectrophotometric determination of anticoccidial drugs; application to multi-ingredient veterinary formulation and computational investigations for multivariate analysis - Abbas, Mahmoud Mohamed; El-Kosasy, Amira Mabrouk; Hussein, Lobna Abd El-Aziz; Hanna, Nancy Magdy (European Journal of Chemistry, 2021)
Simple, accurate, and eco-friendly spectrophotometric procedures were proposed and implemented for simultaneous determination of anticoccidial drugs from three different classes namely, amprolium hydrochloride (AMP), sulfaquinoxaline sodium (SQX) and diaveridine hydrochloride (DVD). Dual wavelength in ratio spectra procedure was proposed where the difference in amplitudes (ΔP) in the ratio spectra at 264 nm and 301.9 nm (ΔP264&301.9 nm) corresponded to AMP with mean percentage recovery 100.00±0.923%, while (ΔP250.9&279 nm) and (ΔP218&243.5 nm) corresponded to SQX and DVD with mean percentage recoveries 99.31±1.083 and 100.64±1.219%, respectively. The dual wavelength in ratio spectra procedure was validated according to the ICH guidelines and accuracy, precision and repeatability were found to be within the acceptable limit. Multivariate chemometric approaches, namely, partial least-squares (PLS-2) and principal component regression (PCR) were also proposed with mean percentage recoveries 99.31±0.769, 98.91±1.192 and 99.04±1.245% for AMP, SQX and DVD, respectively, in PLS-2 and 99.63±1.005, 99.11±1.272 and 98.93±1.338% for AMP, SQX and DVD, respectively, in PCR. These procedures were successfully applied to the multi-ingredient veterinary formulation with mean percentage recoveries 100.75±1.238, 99.29±0.875 and 99.34±0.745% for AMP, SQX and DVD, respectively, in dual wavelength in ratio spectra procedure and 101.03±1.261, 101.48±0.984 and 101.10±1.339% for AMP, SQX and DVD, respectively, in PLS-2 and 100.22±1.204, 101.10±0.546 and 100.91±0.677% for AMP, SQX and DVD, respectively, in PCR.